Axis Dimensional Analysis of Religious Mass Gathering Human Stampede Reports. Issue Volume 34:Issue s1(2019) (May 2019) - Alhadhira, Abdullah A; Molloy, Michael S; Hart, Alexander; Issa, Fadi; Alossaimi, Bader; Fletcher, James; Voskanyan, Amalia; Sarin, Ritu; Ciottone, Gregory R
Abstract : Introduction: Human Stampedes (HS) occur at religious mass gatherings. Religious events have a higher rate of morbidity and mortality than other events that experience HS. This study is a subset analysis of religious event HS data regarding the physics principles involved in HS, and the associated event morbidity and mortality. Aim: To analyze reports of religious HS to determine the initiating physics principles and associated morbidity and mortality. Methods: Thirty-four reports of religious HS were analyzed to find shared variables. Thirty-three (97.1%) were written media reports with photographic, drawn, or video documentation. 29 (85.3%) cited footage/photographs and 1 (2.9%) was not associated with visual evidence. Descriptive phrases associated with physics principles contributing to the onset of HS and morbidity data were extracted and analyzed to evaluate frequency before, during, and after events. Results: 34 (39.1%) reports of HS found in the literature review were associated with religious HS. Of these, 83% were found to take place in an open space, and 82.3% were associated with population density changes. 82.3% of events were associated with architectural nozzles (small streets, alleys, etc). 100% were found to have loss of XY-axis motion and 89% reached an average velocity of zero. 100% had loss of proxemics and 91% had associated Z-axis displacement (falls). Minimum reported attendance for a religious HS was 3000. 100% of religious HS had reported mortality at the event and 56% with further associated morbidity. Discussion: HS are deadly events at religious mass gatherings. Religious events are often recurring, planned gatherings in specific geographic locations. They are frequently associated with an increase in population density, loss of proxemics and velocity, followed by Z-axis displacements, leading to injury and death. This is frequently due to architectural nozzles, which those organizing religious mass gatherings can predict and utilize to mitigate future events.